The Effectiveness of Golden Sea Cucumber Ethanol Extract on The Expression of Endoglin in The Maturation Phase of Healing Mice With Traumatic Ulcers - Rima Parwati Sari; Endah Wahjuningsih (Denta Journal Kedokteran Gigi, 2017)
Background: The traumatic ulcer is the most common oral soft tissue lesion that cause physiologic dissorder (pain) in patients, so it need a medicine to improving healing processs.Stichopus hermanii contains glycosaminoglycans, omega-3 and other agents that accelerate wound healing. Their influence againts signaling cell for proliferation and angiogenic for healing procce. Endoglin plays in a number of cellu- lar processes and the elevated expression during wound healing. Purpose: Knowing the effectivity of ethanol extract of Stichopus hermanii towards the expression on traumatic ulcer maturation phase in oral mucosa. Materials and Methods: The research subjects were forty eight wistar rats divided into 6 groups. Traumatic ulcer was made in the center-rat’s-labial-mucosa. The X1 group was smeared with sterilized aquades as the control group. The X2 was smeared with 0,2% hialuronic acid, X3 with 60% ethanol extract, and X4 with 80% ethanol extract. They were smeared once a day during 4 days. On the sixth day, the rat’s labial mucosa was biopsied to make histological preparation in order to study the amount of fibroblast. Results: Kruskal-Wallis test showed not significant difference (p=0,000) after applying Stichopus hermanii extract for expression of endoglin in Conclusions: ethanol extractStichpus hermanii not effective for expression of endoglin on traumatic ulcer maturation phase in healing procces.